Clinical and functional characteristics of life support systems during and after coronary artery bypass grafting (CARDIOLOGY OF UZBEKISTAN, 2025)
Aim. To evaluate the clinical and functional characteristics of vital systems during and after coronary artery bypass grafting. Materials and methods. This study included 160 patients who underwent CABG with and without cardiopulmonary bypass at the Samarkand branch of the Republican Specialized Scientific-Practical Medical Center of Cardiology (2020–2026). Patients were divided into two groups: the main group (n=80), where an individualized algorithm using a multifactorial prognostic scale and ulinastatin was applied, and the control group (n=80), where standard management was used. Hemodynamic monitoring included HR, mean arterial pressure, CVP, stroke and cardiac indices, ejection fraction, cardiac output, and SVR across six stages from admission to discharge. Results. The main group showed improved outcomes: reduced myocardial afterload, stabilized HR and pressure, enhanced cardiac performance, and a shift from hypodynamic to eukinetic circulation. Conclusion. In high-risk patients, this approach reduced complication rates and ICU stay. An individualized strategy with ulinastatin ensures a more stable perioperative course and lowers complication risk.